Benthic foraminiferal response to the Oceanic Anoxic Event 2 (Late Cretaceous) and evidence of bottom water re‐oxygenation during the Plenus Cold Event at Clot Chevalier (Vocontian Basin, SE France) - Amaglio, Giulia; Petrizzo, Maria Rose; Holbourn, Ann; Kuhnt, Wolfgang; Wolfgring, Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
The Cenomanian-Turonian boundary interval is characterized by environmental perturbations related to the Oceanic Anoxic Event 2 (OAE 2) that severely affected the marine biota, including benthic and planktonic foraminifera. We present a continuous high-resolution benthic foraminiferal record in combination with published planktonic foraminiferal and geochemical data across the Cenomanian-Turonian boundary interval in the Clot Chevalier section (Vocontian Basin, SE France) with the aim to interpret paleoceanographic changes in bottom waters. Benthic foraminiferal assemblages are characterized by low diversity and indicate an outer shelf-upper bathyal environment. Changes in composition and abundance of the benthic assemblages throughout the stratigraphic section allow identification of seven distinct environments. In the middle Cenomanian, below the OAE 2, benthic foraminifera show high species diversity and abundance of infaunal and epifaunal taxa, suggesting an environment characterized by oxic conditions at the seafloor. The microfossil assemblages in the upper Cenomanian within the OAE 2 interval are dominated by radiolaria (> 50%) followed by benthic calcareous taxa (Gavelinella sp., Gyroidinoides sp., Praebulimina elata, Tappanina laciniosa). Benthic agglutinated taxa (Ammobaculites sp., Ammodiscus cretaceus, Gaudryina sp., Textulariopsis bettenstaedti) show high abundance in the lowest part of the OAE 2 and disappear close to the top of the interval. The assemblage composition and the highest values of Total Organic Carbon (TOC) registered in this interval suggest eutrophication and suboxic conditions at the seafloor. However, at ∼1 m above the onset of the OAE 2, the repopulation by inferred oxic benthic foraminiferal taxa (i.e., Frondicularia sp. and Ramulina aculeata) suggests ventilation of bottom water masses, recording the Plenus Cold Event (PCE). In the lowermost Turonian, the assemblages exhibit high species diversity and abundance with the re-appearance of calcareous taxa, indicating oxic ...